THE TYRANNICIDES: A NEW APPROACH TO TEXT AND IMAGE. (October 2021) - Carpenter, Thomas H.
Abstract : The bronze statues of the Tyrannicides, Harmodios and Aristogeiton, by the sculptors Kritios and Nesiotes, set up in the Athenian Agora in 477 bc, were well known to Athenians throughout the classical and Hellenistic periods. In Thucydides' account of the deed of the Tyrannicides, he defines the two as lovers ( erastes and eromenos ), which has led to the assumption that the depictions are in some way likenesses of the two men. I argue that Thucydides' account has been the source of a misreading of the sculptures. Rather, the models for the figures are contemporary representations of the Gigantomachy – Aristogeiton being based on Apollo – and thus, through the allusion to myth, the sculptors created multivalent figures that were emblematic of something that transcended their deed.